Modern Monetary Dynamics: Bids of Money Without Banks, Money Supply Theory, Money Multiplier, and Policy Implications - Siti Nur Rosidah; Dian; Mahmudi jakfar; Muhammad Iklal Hafidzi (Penerbit Hellow Pustaka, 2024)
This research explores modern monetary dynamics with a focus on money supply without bank intermediation, money supply theory, the money multiplier mechanism, and the policy implications arising from this phenomenon. In the contemporary financial context, the emergence of financial technology (fintech) and cryptocurrencies has changed the traditional landscape of money supply, allowing money supply to occur without the direct role of banks. This article discusses the basic concepts of money supply theory, including the factors that affect the money supply in the economy. Furthermore, this study analyzes the money multiplier mechanism, which describes how money injected into the banking system can result in a larger increase in the money supply. Using both theoretical and empirical approaches, this study assesses the monetary policy implications arising from changes in the way money supply occurs, including the challenges for monetary authorities in controlling inflation and financial stability. The results show that this transformation in money supply requires innovative and responsive policy adaptations to maintain the effectiveness of monetary policy in maintaining economic stability.